Combination therapy of N-acetyl-L-cysteine and S-2(2-aminoethylamino) ethylphenyl sulfide for sulfur mustard induced oxidative stress in mice. (2021) - Gupta, Alka; Vijayaraghavan, Rajagopalan; Gautam, Anshoo
Graphical abstract: Highlights: Sulfur mustard, an alkylating agent causes systemic toxicity by dermal application. Decontamination upon contact is the recommended procedure. Percutaneous administration in mice causes oxidative stress. Decrease in glutathione and increase in malondialdehyde are the effects. Combination of NAC and DRDE-07 showed good protection in mice. Abstract: Introduction: Sulfur mustard (SM) is chemically, bis(2-chloroethyl) sulfide and a strong alkylating agent that causes cytotoxicity and blisters on skin. In laboratory animal models, SM is extremely lethal. Since no specific antidote has been proposed, decontamination upon contact is the recommended procedure. Several antidotes have been screened for SM, and in that sulfanyl compounds, N-acetyl-l -cysteine (NAC) and S-2(2-aminoethylamino) ethylphenyl sulfide (DRDE-07) showed good protection. Since they showed protection at high doses, the aim of this study was to evaluate the efficacy in combination at low dose, for percutaneously administered SM in mice. Material and Methods: 4 LD50 of SM (32.4 mg/kg) was administered, and NAC (50 mg/kg), DRDE-07 (25 and 50 mg/kg) and their combinations were evaluated as 30 min pre-treatment by single oral administration. Result: After 72 h of SM exposure, significant decrease in body weight, decrease in hepatic reduced glutathione, and increase in hepatic malondialdehyde were observed (P < 0.001), showing oxidative stress. The combination of NAC (100 mg/kg) and DRDE-07 (50 mg/kg) showed significant protection (P < 0.01). The severe histopathological lesions induced by SM in liver, spleen and skin were also considerably reduced by the combination. Conclusion: The combination of NAC and DRDE-07 having sulfanyl groups, will be promising antioxidants and an effective antidote for SM toxicity.